Central role of obesity in endothelial cell dysfunction and cardiovascular risk - Lima Júnior,José Carlos de (2019)
SUMMARY Atherosclerosis is the leading cause of mortality in the contemporary world. The critical role of the endothelial cells (EC) in vascular homeostasis, the metabolic changes that take place when the cell is activated, and the elements involved in these processes have been widely explored over the past years. Obesity and its impact, promoting a rise in blood levels of free fatty acids (FAs) are often associated with atherosclerosis and cardiovascular mortality. However, the mechanisms that promote cardiovascular structural changes and adaptive changes in the ECs, particularly in the context of obesity, are little known. Here, we reviewed studies that assessed the metabolic adaptations of healthy and dysfunctional ECs during exposure to FAs, as well as the epidemiological perspectives of cardiovascular structural changes in obesity. Finally, we explored the role of new agents – sphingolipids, dietary unsaturated fatty acids and sodium-glucose cotransporter-2 inhibitors (iSGLT2) – in atherosclerosis and their relationship with obesity.